Didactic design for learning social arithmetics based on islamic values at MTS Mu’allimat NW Anjani - Isnaini, Syifa'atul; Isnawan, Muhamad Galang; Shantika, Evana Gina (International Journal of Mathematics and Sciences Education, 2023)
This study aimed to compile a didactic design on social arithmetic material based on learning obstacles and learning trajectories experienced by students when learning the concept. The research method used was a Didactical Design Research (DDR) method with data collection techniques, namely observation, interviews, and learning obstacle tests. The first step in this study was to identify learning obstacles by testing learning obstacle instruments on grade VIII A students, with a total of 18 MTs Mu'allimat NW Anajani students who had received and learned the material. Before the learning obstacle test, researchers first examined the composition of the selected material, namely social arithmetic, in existing source books. Identified, the next step was the preparation of a didactic design with the use of learning theories that were in accordance with the expectations of obstacles when the learning obstacle test could be overcome or reduced. The didactic design that had been prepared was then implemented for grade VIII A students, with a total of 18 MTs Mu'allimat NW Anajani students in the even semester.